Exploring affordances and constraints of blended learning in enhancing life sciences grade 12 learners' understanding of genetics - Matlala, Mpho Nobert (My University, 2024)
The study explored the affordances and constrains of blended learning on enhancing Life Sciences Grade 12 learners understanding of Genetics. The study took place in Limpopo province, Capricorn region under Capricorn South circuit. This study used Situated Learning theory as a theoretical framework and qualitative research approach where single case study served as a design. Furthermore, the study conveniently sampled 22 Grade 12 Life Sciences learners and data was collected through participative observation, semi-structured interviews and document review (written tasks). Among other things the findings of the study revealed that the integration of blended learning afforded learners‘ understanding of Genetics and also caused language constrains among the learners. It was recommended that future studies look into teachers and learners‘ attitudes towards blended learning.
Thesis (M.Ed. (Science Education) -- University of Limpopo, 2024
Keywords: Blended learning (BL); Genetics; Traditional teaching method; Blended learning; Genetics; Environmental education -- Moral and ethical aspects; Life sciences -- Study and teaching